(untitled) (London, Eng., 1959)
The author has divided fishing methods into thirteen categories beginning with fishing without gear. Each category is prefaced by short description and is fully illustrated.
Keywords: Fishing,Fisheries; Equipment and supplies,Equipment and supplies